2021
DOI: 10.4018/ijirr.2021040103
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Diabetes Mellitus With Machine Learning Techniques Using Multi-Criteria Decision Making

Abstract: Diabetes has become one of the common health issues in people of all age groups. The disease is responsible for many difficulties in lifestyle and is represented by imbalance in hyperglycemia. If kept untreated, diabetes can raise the chance of heart attack, diabetic nephropathy, and other disorders. Early diagnosis of diabetes helps to maintain a healthy lifestyle. Machine learning is a capability of machine to learn from past pattern and occurrences and converge with experience to optimise and give decision.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Stress in crops deals with external situations which adversely influence the development or productivity of plants [21]. A plant stress generally reflects a few sudden modifications in the climate situation.…”
Section: Stressesmentioning
confidence: 99%
“…Stress in crops deals with external situations which adversely influence the development or productivity of plants [21]. A plant stress generally reflects a few sudden modifications in the climate situation.…”
Section: Stressesmentioning
confidence: 99%
“…In the survey for our current work, we observed that most of the sensors were generally employed for the prediagnosis and classification of the disease type. We were motivated to implement an integrated environment for dementia patients after the detection of disease to ease the daily activities [ 25 ].…”
Section: Related Workmentioning
confidence: 99%
“…This dataset includes some features that need to be performed in lab like low-density lipoprotein (LDL), and highdensity lipoprotein (HDL). Juneja, A., et al in [12] used the PIMA Indian Diabetes dataset which as we mentioned before includes some features that require lab tests. Muhammad, L. J., et al in [13] used a dataset they collected from the Murtala Mohammed Specialist Hospital, Kano State, in Nigeria, and this dataset also included some features that are lab-related like HDL and triglyceride.…”
Section: Introductionmentioning
confidence: 99%